(untitled) (International Journal of Engineering and Computer Science, 2018)
The term BIG DATA has getting more importance in various industries over last couple of years because industries generated huge amount of data per day. Big Data is applied on various huge and large data sets because it can not be store and process through traditional databases. traditional databases does not have potential to process such large data sets n a reasonable time. Big data has huge potential to store and process such huge and large datasets in several ways because in processing we are analyse the large datasets in a required time. One of the main reason of using R is freely available and its comes with a lots of free packages and powerful tools through which we can easily analyse the large datasets in a sufficient time. Text analysis is still somewhat in its infancy, but is very promising. Because in most of the companies 80% of data is in unstructured form, while most types of analysis only work with structured data. In this paper, we will use R packages to analyze unstructured text.